Revisiting the gonadotropic regulation of mammalian spermatogenesis: evolving lessons during the past decade - Bhattacharya, Indrashis; Dey, Souvik; Banerjee, Arnab (Frontiers in Endocrinology, 2023)
Spermatogenesis is a multi-step process of male germ cell (Gc) division and differentiation which occurs in the seminiferous tubules of the testes under the regulation of gonadotropins – Follicle Stimulating Hormone (FSH) and Luteinising hormone (LH). It is a highly coordinated event regulated by the surrounding somatic testicular cells such as the Sertoli cells (Sc), Leydig cells (Lc), and Peritubular myoid cells (PTc). FSH targets Sc and supports the expansion and differentiation of pre-meiotic Gc, whereas, LH operates via Lc to produce Testosterone (T), the testicular androgen. T acts on all somatic cells e.g.- Lc, PTc and Sc, and promotes the blood-testis barrier (BTB) formation, completion of Gc meiosis, and spermiation. Studies with hypophysectomised or chemically ablated animal models and hypogonadal (hpg) mice supplemented with gonadotropins to genetically manipulated mouse models have revealed the selective and synergistic role(s) of hormones in regulating male fertility. We here have briefly summarized the present concept of hormonal control of spermatogenesis in rodents and primates. We also have highlighted some of the key critical questions yet to be answered in the field of male reproductive health which might have potential implications for infertility and contraceptive research in the future.